ANALISIS PENGARUH ATRIBUT PRODUK DAN ATRIBUT IKLAN TERHADAP MOTIVASI PEMBELIAN SEPEDA MOTOR HONDA VARIO - Nur Fitri Luthfiah; Salamatun Asakdiyah (Universitas Ahmad Dahlan, 2013)
The purpose of this study was to find out product attributes effect and attribute motivation to purchase ads on Honda Vario. The population in this study are all citizens of district Pandak ever bought and used Honda Vario. Sampling technique using purposive sampling. Characteristics of sampled respondents who are residents of districts Pandak ever bought and used Honda Vario motorcycles 17 year old and over. The data was collected by distributing questionaires to a sample of the 100 people. Based on the analysis by t-test of the product attribute variables (X1) obtained the result of probability (0.007), and attribute variables (X2) obtained the probability (0.0001) with significantly the level of 5% (0.05). the probability of two independent variables are smaller than the significance level of 0.05. So based on that analysis can be concluded that the product attributes and attribute partially ads have a significant influence on purchase motivation Honda Vario.